HIV infection and working patient ativity: the etic and legal relation in the vision of the work dentistry - Silva, Luciana N; LG Filho, Douglas; Ferreira, Dennis C (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: the control of HIV infection in the life of the worker infected is responsible for the occupational health’s team in which the labor den-tist is inserted.Objective: this paper aims to clarification for the Surgeon Dentists, mainly those whose job is to monitor the worker’s health, of ethi-cal and legal purposes related to Human Immunodeficiency Virus patients. Methods: was reviewed bibliographic material from scientific periodics,technical books, technical notes, publications of international and national organizations (Medline and Lilacs – in the last ten years). Results:thelabor dentist is attribution responsible for the observation and control of oral manifestations derived from AIDS, as well as the accomplishment ofinformative and preventive campaigns in the companies where they work. Conclusion:the search for technical-scientific knowledge update is provi-ded by law and will grant the professional the necessary confidence to act without prejudice or discrimination, making them able to perform an edu-cational work with the other members of their work and social environment.